Efektivitas Pemanfaatan Dana bagi Hasil Cukai Hasil Tembakau dalam Bidang Kesehatan di Kota Surakarta Tahun 2018 - Febry Wulandari; Waluyo Waluyo (BESTUUR, 2019)
This study describes the application of Tobacco Excise Revenue Funds in Surakarta City and reviews the Efficiency of Use of Tobacco Excise Revenue Sharing Funds specifically in the Health sector in Surakarta City on 2018. This study is normative legal research, applies to provide an assessment that allows to be applied to conclusions that have been taken. This study uses a syllogism method with a deductive mindset. Primary legal material is a regulation that applies authoritatively, secondary legal material consists of books, legal journals, scientific articles and relevant research results and non-legal material consisting of interviews. The technique of receiving legal material in this legal discussion uses document studies and interviews. This study shows that issuing Profit Sharing Funds for Tobacco Excise in Surakarta City in the Health Sector on 2018 is in accordance with Law Number 39 of 2007 and PMK 222/PMK.07/2017 and has run quite effectively starting from financial performance and realization of program activities even though technical and juridical constraints.  Keywords: Excise Revenue Funds, Tobacco, Health, Surakarta City.